TEKS SIWAGAMA SUMBER PELESTARIAN GUNUNG DAN LAUT DI BALI - I Nvoman Weda Kusuma (Program Magister Linguistik Universitas Udayana, 2010)
The Manuscripts bequeathed by the ancestors in Bali amount to thousands. and its content varies. It contains the various aspects of people’s life (cultural traditions), such as: the concepts of leadership, customary rules, order execution ceremony / Yadnya and environmental preservation. Siwagama Manuscript adhered, reveals the various traditions, that is believed, carried out and preserved in the lives of the people of Bali as it is derived from the concepts of Hindu religion. Preservation of mountain and sea conducted by the people of Bali (Hindu) by making the places (sea and mountain) as places to conduct worship, glorify Sang Hyang Widhi (God Almighty) with various manifestations (the Gods) and the places for holding the ceremony / Yadnya. The Ceremony / Yadnya conducted at sea and in mountain by Hindus is called Dewa Yadnya, Pitra Yadnya, and Bhuta Yadnya.